Implementation of Educational Scholarship Programs at Amil Zakat Institutions in West Kalimantan: An Evaluation Study of the CIPP Model - Wardi, Suhra; Sumin, Sumin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Program evaluation is needed to improve the quality of education funding through scholarships for underprivileged students so they can continue quality education. This study aims to evaluate the implementation of educational funding through a scholarship program organized by the Amil Zakat Institute of the Great Mosque of Mujahiddin, West Kalimantan, by using the CIPP model, which consists of context, input, process, and product elements. Program evaluation is carried out through stages, interviews, observation, and documentation. The results obtained are a score of 92.86 and have the